PERAN DUKUNGAN KELUARGA DAN KEBERSYUKURAN TERHADAP KUALITAS HIDUP KELUARGA PADA ORANG TUA DENGAN ANAK BERKEBUTUHAN KHUSUS: Dukungan keluarga, kebersyukuran, kualitas hidup keluarga, anak berkebutuhan khusus - Ikhwanisifa, Ikhwanisifa; Marettih, Anggia Kargenti Evanurul; Susanti, Rita; Raudaful Zahira, Gitsya (Generasi Emas, 2024)
Good quality of family life is vital for parents of children with special needs who often feel stressed and depressed. The quality of family life has a complex effect on parents' physical and psychosocial aspects, which can lead to health problems, family conflicts, and poor living standards. Family support and gratitude are expected to affect the quality of life for families owned by parents of children with special needs. The research subjects were 78 parents in Pekanbaru, determined by purposive sampling. Data collection used an adaptation of the TFQoLS scale (Beach Center on Disability, 2012) Cronbach's alpha 0.937, FSS (Uddin & Bhuiyan, 2019) Cronbach's alpha 0.854 and GQ-6 (McCullough, Emmons & Tsang, 2002) Cronbach's alpha 0.748. Multiple regression results show F= 76.97, R2=0,664, p= 0.00. The results found that family support and gratitude were proven to influence the quality of family life in parents of children with special needs. Gratitude being the best predictor. The study's results showed a correlation between family support, gratitude to the family quality of life. Family support obtained by parents can help ease the burden of parenting, which causes pressure on parents, as well as gratitude which can make parents carry out their roles and responsibilities with a more positive perspective so that family support and gratitude can have an impact positively on the quality of life of families parents of children with special needs. Keywords: family support, gratitude, family quality of life, parents of children with special needs